World trade, child labour, and transnational constitutionalism : the case for a new legal humanism - Humbert, Franziska (World Trade Institute advanced studies ;, 2024)
"This book argues for more coherence between human rights and trade law, analysing the world trade law compatibility of topical trade measures on (forced) child labour such as the US Tariff Act of 1930 or the proposal for an EU Forced Labour Regulation, mainly under the GATT non-discrimination principles and the policy exceptions clause"--